Introduction Pages - Radu E. SESTRAS (Notulae Scientia Biologicae, 2019)
Notulae Scientia Biologicae (http://www.notulaebiologicae.ro), Issue 3, Volume 11, 2019: The papers published in this issue (https://www.notulaebiologicae.ro/index.php/nsb/issue/view/265) represent interesting novelties in different topics of life science. Among the exciting researches, we invite readers to find news about: pharmacological uses and health benefits of ginger (Zingiber officinale) in traditional Asian and ancient Chinese medicine, and modern practice; middle east respiratory syndrome: its occurrence, aetiology, epidemiology, associated clinicopathological findings, diagnosis, prevention and control in humans and animals; ethanolic extract of Chrysophyllum albidum stem bark prevents alloxan-induced diabetes; prevalence of group a rotavirus, some risk factors and clinical signs of the infection in children under five years in Yobe State, Nigeria; prevalence of increased serum urea and creatinine levels in dogs; impact of heat stress on blood and serum biochemistry parameters in rats; acute and sub-acute toxicity of Ganoderma applanatum (Pres.) Pat. extract mediated silver nanoparticles on rat; in-vitro control of oral thrush causal organisms using medicinal plants extracts; generic salmonella in asymptomatic adult volunteers: occurrence, antibiogram, extended-spectrum β-lactamase production and carbapenem resistance; impact of hydrogen peroxide on the secondary metabolites, enzyme activities and photosynthetic pigment accumulation of Vigna unguiculata L. (Walp); diversity, distribution and conservation status of the genus Tectaria Cav. from Deccan Peninsula and western Ghats of India.